Historia języka rosyjskiego: teoria i manipulacja - Pociechina, Jelena (Przegląd Rusycystyczny, 2009)
THE HISTORY OF THE RUSSIAN LANGUAGE: THEORY AND MANIPULATION Summary Models of language competition usually favor the central language over those of the peripheries. Yet the Russian language has failed to establish its hegemony both in the tsarist and Soviet empires. While the tsarist period is briefl y touched upon in the introduction, the present study concentrates on the “missed second opportunity” — the Soviet and post-Soviet period. It attempts to explain the causes for the second failure against a broad historical background, beginning with Lenin’s generous linguistic policy, through the elevation of Russian as the language of the “Soviet People” and of the “Communist Future” in the post-Stalin period, to the current (1992) retreat under local and global challenges. The role of language grievances in promoting national self-assertiveness and causing the present anti-Russian backlash in the republics is highlighted. The paper ends with a discussion of the future prospects of Russian as a second language. HISTORIA JĘZYKA ROSYJSKIEGO: TEORIA I MANIPULACJA Streszczenie Modele kompetencji językowej zazwyczaj faworyzują język centralny na tle języków z obszaru peryferyjnego. Jednakże język rosyjski nie zdołał ustanowić własnej hegemonii ani w imperium carskim, ani w sowieckim. Chociaż okres carski jest we wstępie pokrótce omówiony, to niniejszy artykuł skupia się na „niewykorzystanej drugiej szansie” — okresie sowieckim i postsowieckim. Podjęta zostaje tu próba wyjaśnienia przyczyn owego niepowodzenia na szerokim tle historycznym, począwszy od polityki językowej Lenina, poprzez wyniesienie języka rosyjskiego jako języka „Ludu Sowieckiego” i „Komunistycznej Przyszłości” w okresie poststalinowskim, aż po obecne (1992) wycofanie się w wyniku lokalnych oraz globalnych wyzwań. Uwypuklona jest tu rola językowego poczucia krzywdy, jeśli chodzi o promowanie narodowej pewności siebie i powodowanie gwałtownego sprzeciwu antyrosyjskiego manifestowanego w republikach rosyjskich. Artykuł kończy dyskusja nad przyszłymi perspektywami języka rosyjskiego jako języka obcego.